Discotische Flüssigkristalle mit neuartigen Lateralfunktionen - Bernd Kohne; Peer Marquardt; Klaus Praefcke; Panicos Psaras; Werner Stephan (CHIMIA)
Four novel types of non-centrosymmetric discogenic inositol derivatives (4b, 5b, 7a, and 7b) with each two or three different kinds of lateral functions have been synthesized and studied by optical microscopy and thermal analysis. Among them is the first thermotropic, discotic liquid crystalline alcohol (4b) and thiol (7a) which have been obtained by an intramolecular aminolysis of the 1 -amino-1-deoxy-scyllo-inositol intermediate 2b in analogy to the model reaction via 2a or by Pummerer reaction from the monothioscyllitol-S-oxide derivative 6, respectively. These two compounds 4b and 7a as well as the methoxy and acetylthio derivatives 5b and 7b exhibit wide ranges of thermotropic discotic mesophases. The possibilities these results promise for further synthetic work in the field of disc-shaped liquid crystals and conceivable applications of those compounds are discussed.